2012
DOI: 10.1007/s00417-012-2066-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes of axial length measured by IOL master during 2 years in eyes of adults with pathologic myopia

Abstract: The measurement by IOL Master in a large population of highly myopic patients clearly showed that the axial length continued to increase in a span of 2 years even in the 4th decade of life. The eyes with longer axial length showed a greater increase of axial length, suggesting the possibility that the more myopic eyes become more myopic with increasing age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 6 publications
3
33
0
2
Order By: Relevance
“…To note, the presence of CNV and being female contributed to greater changes in the axial length per year. The study by Saka et al, in which changes in the axial length were examined using the IOLMaster, similar to our study, reported that a longer axial length at the initial examination resulted to a greater changes in the axial length per year [7]. However, in our stepwise analysis, the axial length at the initial examination was not selected.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…To note, the presence of CNV and being female contributed to greater changes in the axial length per year. The study by Saka et al, in which changes in the axial length were examined using the IOLMaster, similar to our study, reported that a longer axial length at the initial examination resulted to a greater changes in the axial length per year [7]. However, in our stepwise analysis, the axial length at the initial examination was not selected.…”
Section: Discussionmentioning
confidence: 53%
“…However, A-scan ultrasonography was used in their study. Later, Saka et al, used the IOLMaster, which allows more accurate and non-invasive measurements of the axial length, to examine 185 eyes of 185 high myopia patients (mean age at the initial examination, 48.4 ± 12.2 years) without a history of intraocular surgery and any active fundus diseases, and observed a significant increase in the axial length from 29.35 ± 1.80 mm to 29.48 ± 1.85 mm over a 2-year period [7]. The highly myopic eyes with no complications group in our study also showed an increase of mean axial length from 29.01 ± 1.6 mm to 29.11 ± 1.6 mm, supporting the results of Saka et al However, their reported changes in the axial length per year was 0.06 mm, which is greater than that found in our study of 0.04 mm per year.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thank you very much for your interest concerning our recent paper reporting the changes of axial length in eyes of adults with pathologic myopia [1]. This study relates to our earlier study which examined the long-term change of axial length in eyes with pathologic myopia by using A-mode echography [2].…”
Section: Dear Editormentioning
confidence: 91%